2006
DOI: 10.1111/j.1542-474x.2006.00122.x
|View full text |Cite
|
Sign up to set email alerts
|

Heart Rate Variability in Young Women with Polycystic Ovary Syndrome

Abstract: Autonomic innervation of the heart can be affected in PCOS with increased sympathetic and decreased parasympathetic components of HRV. As a result, sympathetic to parasympathetic ratio may increase in PCOS. This finding should be confirmed with larger studies also evaluating the clinical implications of altered HRV parameters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
76
4
9

Year Published

2007
2007
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(104 citation statements)
references
References 43 publications
(106 reference statements)
9
76
4
9
Order By: Relevance
“…In this study, we found that women with PCOS have reduced cardiac autonomic modulation, as demonstrated in previous studies [3][4][5][6], and ANS fluctuation was reduced in their stimulated ovulatory cycles.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…In this study, we found that women with PCOS have reduced cardiac autonomic modulation, as demonstrated in previous studies [3][4][5][6], and ANS fluctuation was reduced in their stimulated ovulatory cycles.…”
Section: Discussionsupporting
confidence: 62%
“…Although the etiology of PCOS is not exactly known, some have argued that stress and adrenergic activation might be playing a role in its development [2]. It has been demonstrated in previous studies that there is an increase in the sympathetic nerve activity of women with PCOS [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that autonomic innervation of the heart may be affected in PCOS with increased sympathetic and decreased parasympathetic components of heart rate variability (39). In a recent study of 75 women with PCOS and matched controls heart rate recovery, a measure of autonomic dysfunction associated with increased mortality was impaired in PCOS after maximal cardiopulmonary exercise testing, and was inversely related to BMI (40).…”
Section: Cvr Markers By Imagingmentioning
confidence: 99%
“…In the study group, the test was conducted during amenorrheic period 7 . The subjects were asked to report to AFT laboratory at 07.00 hours after overnight fasting.…”
Section: Methodsmentioning
confidence: 99%
“…With this potent comorbid factor, PCOS poses a significant cardiovascular (CV) risk which warrants an early assessment of CV health of patients suffering from this condition 5 . A significant relation between the adverse CV events and autonomic dysfunction has been evidenced from previous studies 6. Few studies have reported CV autonomic involvement in the form of decreased heart rate variability (HRV) and increased sympathetic tone in patients with PCOS 7,8 . But no studies have been conducted till date on the detailed assessment of the reactivity of the sympathetic and parasympathetic division of the autonomic nervous system in PCOS.…”
Section: Introductionmentioning
confidence: 99%